(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Eclampsia is a common obstetrical emergency, remains a leading cause of maternal and perinatal morbidity and mortality in Bangladesh. Combined Intramuscular (IM) and Intravenous (IV) regime of MgSO4 is commonly used in the treatment of eclampsia. However, IM loading dose of MgSO4 could be a suitable al ternative for community intervention of the management of eclampsia. This study aimed to compare the efficacy of theloading total IM regime of injection MgSO4 with the standard loading combined IV and IMregime for prevention of recurrent convulsions in the treatment of eclampsia. Materials and methods: Anopen labeled randomized clinical trial was conducted in the Department of Obstetrics and Gynaecology, Chittagong Medical College Hospital, Bangladesh from January 2017 to December 2017 including 120 patients with eclampsia. Patients were randomly allocated to either of the two groups: one group received standard loading combined IV and IM regime and other group received loading IM regime. The primary outcome measure was the rate of recurrent convulsions. Results: Both the groups were comparable in terms of their baseline demographic, obstetric and clinical characteristics. The recurrent convulsion rate was similar in two groups (15% vs.13.3%, p=0.756). The mean number of recurrent convulsion was 1.67±0.71 and 1.88±1.12 in IM and IM+IV group, respectively (p=0.65). Maternal mortality was 1.7% in both groups. Live birth rate was 85% in IM and 80% in IM+IV group (p=0.542) and low APGAR score at 5 minutes was found in 60.8% and 62.5% of the neonates in IM and IM+IV group, respectively (p=0.558). Conclusions: Loadingtotal IM regime of MgSO4 was found equally effective to the loading combined IV and IM regime in terms of prevention of recurrent fits in eclampsia. So it could be used by the field level workers before referral. Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 31-35